Infant mortality and the role of seigneurial tenure in Canada East, 1851 - Alex Arsenault Morin; Vincent Geloso; Vadim Kufenko (Universität Hohenheim, 2015)
This paper aims to explain differences in infant mortality across the colony of Quebec, known in the 1850s as Canada East, by institutional settings. Areas settled under French laws (known as seigneurial law) implied important transfers from peasants to landlords through private taxes and duties, restrictions on mobility, scant provision of public goods and disincentives to invest in agricultural productivity. As a result, areas under this law system tended to be poor and prone to high mortality. Upon conquering Quebec, the British maintained French land laws but, in 1791, the boundaries of its application were frozen - all newly settled lands would be under British land laws. By 1851, the two legal systems had cohabited for six decades - allowing us to compare them. Using the 1851 census, we argue that French seigneurial law - which reduced living standards through a variety of channels - translated into higher rates of infant mortality. After estimating a Zero-inflated Negative Binomial Regression we find that the effect of seigneurial tenure results in an increase in infant death rates from 43.79 to 44.89 for the age group below one and from 5.21 to 5.277 for the age group from one to five. Additionally, we conduct robustness checks by limiting the sample to large settlements and changing the age groups for the dependent variable.
urn:nbn:de:bsz:100-opus-11660
Keywords: 330